2022
DOI: 10.1007/s12325-022-02296-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of Treprostinil Palmitil Inhalation Powder for Pulmonary Hypertension: A Phase 1, Randomized, Double-Blind, Single- and Multiple-Dose Study

Abstract: x the mean (CV%) of C max , C min , and AUC s were 193-228 pg/mL (32.9-46.4%), 17.6-22.8 ng/mL (43.7-64.4%), and 1680-1820 pgÁh/mL (28.7-36.6%), respectively. The elimination t 1/2 was 6.84-8.82 h after repeat dosing. No steadystate accumulation was observed. Plasma concentrations of TP were below the limit of quantification (100 pg/mL) at all time points measured. Conclusion: TPIP was well tolerated at the doses tested, and dose titration improved tolerability. Treprostinil pharmacokinetics were linear and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a phase I study, treprostinil palmitil inhalation powder (TPIP) demonstrated a safety profile and good tolerability. Also, pharmacokinetic studies indicated the potential for once-daily administration [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I study, treprostinil palmitil inhalation powder (TPIP) demonstrated a safety profile and good tolerability. Also, pharmacokinetic studies indicated the potential for once-daily administration [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…TPIP was first evaluated in human subjects in a phase Ib study to evaluate safety and tolerability of the drug. 38 Subjects were randomized to single or multiple (7 days) daily doses. Treatment-emergent adverse events largely consisted of cough, headache, and nausea, and upward dose titration appeared to reduce the incidence of adverse events compared to initiation at high dose.…”
Section: Treprostinil Palmitil Inhalation Powder (Tpip)mentioning
confidence: 99%